'Comfort women must fall'? Japanese governmental responses to 'comfort women' statues around the world. (December 2021) - Ushiyama, Rin
This article examines Japanese governmental responses to memorial statues dedicated to 'comfort women' – women across the Asia-Pacific whom the Japanese military forced into conditions now recognised as sexual slavery before and during World War Two. This article discusses four cases around the world in which Japanese government officials have demanded the removal of comfort women statues: 1) Glendale, California; 2) San Francisco; 3) Manila; and 4) Berlin. The global expansion of comfort women memorialisation is significant to contemporary statue politics and crises of memory in three ways. Firstly, East Asian diasporas have become important actors in the remembrance of Japanese colonialism and the Asia-Pacific War outside East Asia. Secondly, these statues constitute attempts by diasporas to recover and reclaim a traumatic past through material culture. Thirdly, despite the global geographical reach of comfort women memory activism, neither nationalism nor the power of the nation-state have declined in today's transnational world.